Floristic Composition of Weed Community in Turf Grass Area of West Peninsular Malaysia - Md Kamal Uddin,; Juraimi, Abdul Shukor; Begum, Mahfuza; Ismail, Mohd Razi; Abd Rahim, Anuar; Othman, Radziah (2009)
A survey was conducted at 50 different types turfgrass field such as football field, rugby field, hockey field, turf nursery, lawn area, landscape area, recreational park area, green golf and fairway golf in Malaysia during November-December 2007 to identify most common and prevalent weeds associated with turf grass. The turf grass areas were covered by four turf viz. Axonopus compressus (carpet grass), Cynodon dactylon (tifdwarf), Zoysia matrella (Manilla grass) and Paspalum vaginatum (seashore paspalum). Fields surveyed were done according to the quantitative survey method by using 0.5 m x 0.5 m size quadrat with 20 samples from each field. The data were summarized using five quantitative measures viz frequency, field uniformity mean fields density, mean occurrence field density and relative abundance. A total of 79 different weed species belongs to 16 families were identified of which 43 annual and 36 perennial; 30 grassy weeds, 17 sedges and 32 broadleaf weeds. Cyperus aromaticus, Fimbristylis dichotoma, Chrysopogon aciculatus and Borreria repens were most frequent species covering more than 50% fields. Based on relative abundance indices, perennials were more dominant than annuals. C. aromaticus, F. dichotoma, Desmodium triflorum, Ischaemum indicum, C. aciculatus and B. repens were more prevalent and abundant species out of 10 most weed dominant species in turf grass areas.